Preparation and Identification of Some New Heterocyclic Derivatives from Suberoyl Chloride and Their Study as Anti-bacterial - Abed Abdul‐Reda , Nabeel; Hassan jebur, Miad (Al-Qadisiyah Journal of Pure Science, 2019)
Some new derivatives ofsuberic chloride synthesized by reactionssuberoyl chloride with 4-amino acetophenoneto prepare N1,N8-bis(4-acetylcyclohex-2-en-1-yl)octanediamide,then react with 4-nitrobenzaldehydein the presence of sodium hydroxide,the product reacted with (urea,thiourea, phenyl hydrazine, 2-amino aniline,2-aminophenol, 2,4-dinitrophenyl hydrazine and 2-amino benzothiol) to prepare many hetrocyclicderivatives. This reaction was checked by thin‐layer chromatography (TLC) method. All new compounds were characterized by melting points, elemental analysis, FT‐IR,1H&13C-NMR. The antibacterial action of these derivatives was determined.